Effect of Priming on Germination Traits and Antioxidant Enzymes of Pumpkin (Cucurbita pepo L.) Seeds with Different Vigor under Drought Stress - Omid Sofalian; Raouf Seyed Sharifi; Mohammad Sedghi; Parisa Jahed (Journal of Agricultural Sciences)
Drought stress is a critical environmental stress that limits the productivity and sustainability of agriculture in arid and semi-arid regions by reducing the germination rate and delaying the start of germination and seedling establishment. There are various methods to increase the yield of agricultural plants, each of which somehow improves the yield of seeds in terms of germination indicators and seedling establishment. One of the most common methods to increase poor seed germination is priming before planting. To investigate the effects of priming on aspects of germination of aged pumpkin seeds under drought stress, a factorial experiment was conducted based on a completely randomized design with four replications in the laboratory. Treatments that include seed aging (control, 85% and 75% of control germination), drought stress (0, -0.75 and -1.5 MPa), and priming (control, hydro, gibberellin, GR24, benzyl aminopurine and spermidine). The results of a mean comparison between drought stress, seed ageing and priming showed that the lowest germination percentage (GP) of pumpkin (43.6%), protein (0.82 mg.g-1Fw), radical length (RL, 9.24 mm), plumule length (PL, 1.19 mm), relative water content (RWC, 35.5%), carotenoid (1.253 mg.g-1Fw), catalase (CAT, 7.03 µmol.gmin-1.mgprotein-1), peroxidase (POX, 47.72 µmol.gmin-1.mgprotein-1) and superoxide dismutase activity (SOD, 53.48 mmol.gmin-1.mgprotein-1) were associated with drought treatment at -1.5 MPa and with 75% aging in the absence of priming. In addition, the lowest content of malone dialdehyde (MDA, 3.75 mmol.g-1Fw) and proline (1.573 µg.g-1Fw) were obtained from the absence of drought and aging with priming using spermidine. The highest GP (98.03%) and protein (9.54 mg.g-1Fw) were obtained from gibberellin treatment, RL (15.73 mm) and PL (4.26 mm) in priming using GR24 hormone, RWC (83.64%), carotenoid (6.277 mg.g-1Fw), CAT (40.44 µmol.gmin-1.mg protein-1), POX (95.71 µmol.gmin-1.mgprotein-1) and SOD activity (131.68 µmol.gmin-1.mg protein-1) in priming with spermidine with non-drought stress and aging conditions. The highest MDA (32.42 mmol.g-1Fw) and proline (0.55 µg.g-1Fw) were observed in drought conditions with an intensity of -1.5 MPa and 75% aging in the absence of priming.